Social Media Marketing and Brand Awareness of Customers: Evidence from Nepal - Lamichhane, Basu Dev; Lama, Padam Bahadur; Pandey, Prerna; Lamichhane, Saujan; Rai, Kussum; Shrestha, Barsha (Nepal Journal of Multidisciplinary Research, 2025)
Background: Social media marketing is a vital promotional strategy of business entities that contributes to enhance brand awareness among the customers. The outcome variables encompasses brand awareness behaviour of clients and influencer variables comprise advertisement, electronic word of mouth, and social media interaction. Objective: This study aims to investigate the influence of social media marketing on brand awareness. Thus, study variables of the study consists of advertisement, electronic word of mouth and social media interaction as independent variable and brand awareness as dependent variable. Methods: This study employed the descriptive and casual relational research approach. The investigation delves deep into the intricate interplay between various dimensions of social media marketing and brand awareness. s. The primary information utilized in the study consisted of a total of 119 (58.33 percent) questionnaires that were found useful out of 204 disseminated questionnaires. Findings: The findings of the study revealed a positive and significant influence of advertisement on brand awareness (β = 0.677, p <0.05). Similarly, a positive and significant effect of electronic word of mouth found on brand awareness (β = 0.067, p <0.05). Finally, results depicted a positive and significant influence of media interaction on brand awareness (β = 0.649, p <0.05). Conclusion: Further, the study's findings extend beyond clients to encompass all individuals seeking to enhance brand awareness. The research probes into the interconnected nature of various dimensions of social media marketing, indicating that a combined or adaptive approach may produce the most effective results in enhancing overall brand awareness. It is evident that by acknowledging the influence of social media marketing on brand awareness. Manufacturers and distributors of products and services and other business entities can adopt these findings while deciding on sales and marketing strategies. Novelty: The study provides empirical evidence of social media marketing on brand awareness. Despite the several previous studies conducted in social media marketing, inconsistent findings exist and rare evidences are explored in the Nepalese context.